2020
DOI: 10.1017/s0144686x20001725
|View full text |Cite
|
Sign up to set email alerts
|

‘She shouldn't cross the line’: experiential effectivity of social guidance trajectories for socially isolated older adults with complex problems

Abstract: Social isolation of older adults is difficult to break through, and interventions that focus on network development or enhanced social participation are hardly effective, especially when the older adults have been isolated for a long time and have problems in multiple life domains. This study aimed to investigate the needs and subjective experiences of this less-researched group and obtain a deeper understanding of their goals and priorities. The study involved a qualitative study with 25 socially isolated per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For example, the strong need for control of the socially older adults leads to the rejection of help and interference, while they have a strong need to talk about their lives and their situation. These findings are relevant because evaluation studies show that interventions for socially isolated older adults produce hardly positive results (Dickens et al, 2011;Machielse, 2015Machielse, , 2022Gardiner et al, 2018;Machielse and Duyndam, 2021;Beckers et al, 2022). Knowledge of meaning needs can help improve the quality of support for this target group.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the strong need for control of the socially older adults leads to the rejection of help and interference, while they have a strong need to talk about their lives and their situation. These findings are relevant because evaluation studies show that interventions for socially isolated older adults produce hardly positive results (Dickens et al, 2011;Machielse, 2015Machielse, , 2022Gardiner et al, 2018;Machielse and Duyndam, 2021;Beckers et al, 2022). Knowledge of meaning needs can help improve the quality of support for this target group.…”
Section: Discussionmentioning
confidence: 98%
“…However, our participants’ experience reflected that stigmatization and criminalization of drug use is still common in Hong Kong and imposed negative impact on their cessation motivation. Social isolation and a feeling of loneliness are common among older populations, and the stigmatization and criminalization of drug use has reinforced such a feeling among older individuals with SUD (Machielse, 2020). This finding is in accordance with previous studies that indicate the negative influence of social stigma and social isolation on individuals with SUD’s willingness to seek treatment and maintain abstinence (Askew & Bone, 2019; Foster et al, 2021; Hammarlund et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Second, some life events are less likely to be experienced by individuals until they are older. Gerontologists have found that many of these later life events—such as the aging of the physical body, social isolation, and retirement—negatively impact older persons (Kristensen et al, 2021; Machielse, 2020; Matheson et al, 2019). Research about the impact of these later life events on the motivation of individuals with SUD to cease illegal drug use (hereafter referred to as “cessation motivation”) remains limited, and thus requires additional scholarly attention.…”
Section: Introductionmentioning
confidence: 99%
“…They can only help them if they not only understand the perspective and logic of their clients, through imagination, but also feel the needs of the client. This requires the expertise to empathise with the other that is to recognise the client's emotions (sadness, desperation, disappointment) and to feel in a potential way or modus what the client is actually experiencing (Van Dijke et al, 2018, 2020.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…Most clients were also interviewed by the main researcher. The experiences of the clients are at the heart of another article (Machielse, 2020).…”
Section: Logbooks Of the Social Workersmentioning
confidence: 99%